Metacognitive Reading Strategies of EFL University Students - Suharni, Suharni; Sesmiyanti, Sesmiyanti; Perpisa, Lili; Putri, Anisa (Journal of English Language and Education, 2024)
This present paper reports finding from a study dealt with the English as a Foreign Language (EFL) students’ metacognitive reading strategies. A total of 68 students were selected enrolled in English department of private university in West Sumatra and they were asked to complete a survey. However, after analysing the data, only the data from 38 students as participants could be included in the report. In this quantitative survey, the instrument used to gather data was based on a Survey of Reading Strategies (SORS). The study’s findings revealed that the Global Reading Strategies was the most frequently used, followed by the Support Reading Strategies and the Problem-Solving Strategies. Furthermore, implications of the finding are discussed in relation to reading comprehension of foreign language teaching and learning.